Professionalism kills the trading star: Explaining member participation in trading communities - BENOIT, Sabine (Institutional Knowledge at Singapore Management University, 2019)
Trading communities provide non-commercial members with an online platform on which to exchange goods. Its success depends on member participation; however, little is known about its drivers. Based on literature we identify five drivers. To capture their impact over time,we test a latent growth curve model with longitudinal data, comparing the effects at an initial point of time with their impact on the growth of member participation over three subsequent periods. The results show that providers’ responsiveness and community identification have a positive effect on the initial level, but not on growth. Members’ enjoyment has no level effect, but a growth effect. Only role clarity has an impact on level and growth. Interestingly, co-members’ cooperation weakens member participation, which leads us to conclude that too much cooperation – which appears as professionalism in a trading community – ‘kills’ member participation. We conclude with theoretical and managerial implications.